Association between loneliness and cognitive function, and brain volume in community-dwelling elderly - Lee, Hunju; Yong, Sang Yeol; Choi, Hyowon; Yoon, Ga Young; Koh, Sangbaek (Frontiers in Aging Neuroscience, 2024)
Introduction We investigated the relationship between loneliness, cognitive impairment, and regional brain volume among elderly individuals residing in the Korean community. Methods Data from the ARIRANG aging-cognition sub-cohort, collected between 2020 and 2022, were utilized for the present study. Loneliness was assessed using the UCLA-Loneliness Scale (UCLA-LS) questionnaire and the relevant item from Center for Epidemiologic Studies Depression Scale Korean version (CES-D-K). Cognitive impairment was measured through Mini-Mental State Examination (K-MMSE-2) and Seoul Neuropsychological Screening Battery (SNSB-C), with five sub-categories: attention, memory, visuospatial function, language, and executive function. Logistic regression was employed for prevalence ratios related to cognitive impairment, while linear regression was used for regional brain volume including white matter hyperintensity (WMH) and cortical thickness. Results Our analysis involved 785 participants (292 men and 493 women). We observed increased cognitive impairment assessed by K-MMSE-2 [UCLA-LS: odds ratio (OR) 3.133, 95% confidence interval (CI) 1.536–6.393; loneliness from CES-D: OR 2.823, 95% CI 1.426–5.590] and SNSB-C total score (UCLA-LS: OR 2.145, 95% CI 1.304–3.529) in the lonely group compared to the non-lonely group. Specifically, the lonely group identified by UCLA-LS showed an association with declined visuospatial (OR 1.591, 95% CI 1.029–2.460) and executive function (OR 1.971, 95% CI 1.036–3.750). The lonely group identified by CES-D-K was associated with impaired memory (OR 1.577, 95% CI 1.009–2.466) and executive function (OR 1.863, 95% CI 1.036–3.350). In the regional brain volume analysis, loneliness was linked to reduced brain volume in frontal white matter (left: −1.24, 95% CI −2.37 ∼−0.12; right: −1.16, 95% CI −2.31 ∼ −0.00), putamen (left: −0.07, 95% CI −0.12 ∼−0.02; right: −0.06, 95% CI −0.11 ∼−0.01), and globus pallidus (−15.53, 95% CI −30.13 ∼−0.93). There was no observed association in WMH and cortical thickness. Conclusion Loneliness is associated with cognitive decline and volumetric reduction in the frontal white matter, putamen, and globus pallidus.